Redesigning traditional weed management practices in faba beanfields to optimize food-feed production in the smallholder system - Bezabih, Melkamu; Mekonnen, Kindu; Adie, Aberra; Tadesse, Tamene; Nurfeta, Ajebu; Dubale, Workneh; Habiso, Tesfaye; Kelkay, Tessema Z.; Getnet, Million; Ergano, Kebebe; Duncan, Alan J.; Thorne, Peter J. (Wiley, 2022)
Duringthe main cropping season, Ethiopian farmers deliberately weed faba bean (Vicia faba L.) fields much later than recommended and use the weed herbage mass as feed. This study examined the rationale behind farmers’ practices and explored options to further improve productivity. The study involved two experiments. The first compared the overall benefit from the traditional weed management regime against the frequent weeding recommendation. Sixty farmers participated, each preparing two plots. The plots were randomly assigned to either traditional (one late weeding) or improved (two early weeding) management. The second examined the suitability of intercropping faba bean with oat (Avena sativa L.). It involved a 5 × 3 factorial experiment, three management practices (traditional, improved, and faba bean oat intercropping) and five faba bean varieties repeated over 3 yr. In the first experiment the improved weed management increased grain yield (2.49 vs. 2.12 Mg ha–1) compared to the traditional. But the traditional management produced higher (P < .01) weed forage biomass (2.12 vs. 0.27 Mg ha–1) compared to the improved. The analysis showed the opportunity costs associated with the loss in weed forage biomass were not convincingly offset by the economic gains from increased grain yields. In the second experiment, grain yield was again highest for the improved weed management and lowest for the intercropping. Analysis of economic returns revealed that the intercropping management provides greater benefit over the traditional management practice. Farmers’ decisions have a rational economic basis and building on the traditional practicewith improved forage intercropping would allow to further optimize productivity.